Analysis of the Effectiveness of Cold Therapy (Ice Compress) on Reducing Patient Pain Intensity - Fitriani. K; Rezqiqah Aulia Rahmat; Sahalia Sahalia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Pain is a physiological and psychological response often experienced by patients due to trauma, inflammation, or medical procedures. Non-pharmacological therapies such as ice compresses (cold therapy) are widely used as simple interventions to reduce pain. This study aims to analyze the effectiveness of cold therapy in reducing pain intensity in patients. The study used a quasi-independent design. experiment with a pretest – posttest approach without control group . A sample of 40 patients with complaints of mild to moderate acute pain was selected using purposive sampling. Pain intensity was measured using Numeric Rating Pain Scale (NRS) before and after applying ice compresses for 15 minutes. Data analysis used a paired t- test . The results showed a significant decrease in pain scores from 6.2 ± 1.1 to 3.4 ± 1.0 (p < 0.001). It was concluded that cold therapy is effective in reducing pain intensity and can be used as a supporting intervention in pain management. Keywords: Cold Therapy, Ice Compress, Pain, Nonpharmacological Intervention